Analysis of Corporate Strategy, Business Risk, and Managerial Ownership on Company Performance with Capital Structure as a Mediating Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Annisa Nur Rizka Sukanto; Jubaedah Nawir; Desmintari Desmintari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to Analysis of Corporate Strategy, Business Risk, and Managerial Ownership on Firm Performance with Capital Structure as a mediation variable in Manufacturing Companies on the IDX. The population in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 that conduct export transactions and have managerial ownership, totalling 51 companies. Due to the small sample size, the full sampling technique was used, resulting in a total of 255 observations. Data analysis was performed using the panel data regression method processed with EViews version 12. The research result are as follows: (1) Vertical integration strategy does not affect company performance, (2) Diversification strategy affects company performance, (3) Internationalization strategy affects company performance, (4) Business risk does not affect company performance, (5) Managerial ownership affects company performance, (7) Capital structure is not proven as a mediating variable because it cannot mediate the influence of vertical integration strategy, diversification strategy, internationalization strategy, business risk, and managerial ownership on the performance of manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2023 research period.